Advances in forensic human identification - Mallett, Xanthe; Blythe, Teri; Berry, Rachel (CRC Press/Taylor & Francis Group, 2014)
The book examines online, sexual, and biometric identities and discusses problems associated with investigative practice, such as the developing use of the Internet as a distribution and communication medium for criminal activities. It also explores miscarriages of justice that can result from flawed applications or interpretations of forensic evidence.